Exploring a lecturer’s reader-response strategy to foster university students’ critical thinking - Adila Yohana; Lilies Youlia Friatin; Luthfiyatun Thoyyibah (Universitas Galuh, 2026)
Critical thinking is a vital 21st-century skill, yet many Indonesian students struggle to develop higher-order thinking abilities. This study investigates the use of the reader-response strategy to stimulate university students’ critical thinking, particularly in areas such as interpretation, analysis, and evaluation. The study aims to examine how the lecturer implements the strategy, identify the challenges faced, and explore students’ perceptions of its effectiveness. A qualitative case study design was employed. Data were gathered through non-participant observation, a semi-structured interview with a lecturer, and a questionnaire distributed to 24 students enrolled in an Introduction to Literature course. Thematic analysis was used for the observation and interview data, while exploratory data analysis was applied to the questionnaire responses. The findings revealed that the lecturer implemented various reader-response activities, such as personal reflection, written responses, interpretive freedom, and classroom discussion—encouraged students to analyze textual meaning, justify interpretations, and consider multiple perspectives. These are core aspects of critical thinking. However, some students remained passive or reluctant to express opinions. The lecturer addressed this by using scaffolding strategies and small-group discussions. Most students stated the strategy improved their text comprehension, confidence in sharing ideas, and class participation. Based on the findings, the study concludes that the reader-response strategy effectively supports the development of critical thinking in EFL literature classrooms when combined with appropriate instructional support.